Snakes and stone, sullied and cone myths about women in the 2009 Darna television series. - Atis, Allison Anne G.; Aguirre, Alwin C.
This study examines the 2009 Darna television series and situates Darna as a cultural text, dissecting its portrayal of womanhood and the intersections of myth, genre, and gender discourses. By contextualizing the myths within the local television superhero genre, the study analyzes how they operate within broader historical, cultural, and socio-political frames. The literature review expands on the inquiry’s important intersections: Darna as a text, its genre, and the mythologizing of womanhood, establishing the study’s relevance through critical notions on the historicity of the Filipina, superhero discourses, and representations of women in media and popular culture. The study employs a multifaceted framework incorporating Roland Barthes’s theory of myth, genre, discourse analysis, and postmodern feminism. Through critical textual analysis, the myths are identified, analyzed, and linked to several frames and contexts, which therefore reveal the persistent binaries in women’s representations, emphasizing the interplay of power, gender roles, and societal expectations. These contradictions reveal not only how myth’s dynamic with genre conventions work to sustain gender constructs, but also the broader cultural push and pull between progress and tradition. Ultimately, this study underscores the enduring relevance of myths in shaping gender narratives and calls for further exploration of how myths evolve within contemporary media texts.